Coagulopathy and extensive local swelling following Green pit viper (Trimeresurus trigonocephalus) envenoming in Sri Lanka. (April 2017) - Namal Rathnayaka, R.M.M.K.; Kularatne, S.A.M.; Ranathunga, P.E.A.N.
Abstract: Trimeresurus trigonocephalus (Sri Lankan Green pit viper) is a moderately venomous arboreal snake endemic to Sri Lanka. Even though, its bites are not uncommon, published reports of such cases are limited to three in literature. We report three cases of coagulopathy following Green pit viper bites and treatment with fresh frozen plasma. Highlights: Three cases of Sri Lankan Green pit viper ( T. trigonocephalus ) bites are described. All had incoagulable blood lasting for days and extensive local swelling. Administration of fresh frozen plasma probably restored coagulation. This is the 4th report of T. trigonocephalus bites in Sri Lanka.